Overview Of the Students’ Perception of The Impact of Extracurricular Activities on Academic Performance in Rajshahi University - Malik Senjuti, Rayhana; Fuad, A Z M (South Asian Journal of Social Sciences and Humanities, 2025)
Engaging in extracurricular activities holds a pragmatic role in shaping students’ academic performance, self-development, and future career prospects. This study investigates perceptions, experiences and challenges which Rajshahi University students are facing regarding their involvement in ECAs and its impact on their academic success. This research study has taken qualitative research approach using semi-structured interviews and focus group discussions (FDGs) along with the students actively participating in various ECAs, including cultural organizations, sports, debate clubs, and social service groups of Rajshahi University. The findings reveal that, ECAs enhance students’ cognitive development, leadership skills, networking abilities, and academic engagement as well. However, academic pressure, time constraints, and lack of institutional support are the reason of their hindrance. The findings further reveal the Parental and institutional support that significantly influences students’ engagement. Nevertheless, excessive involvement in extracurricular activities (ECAs) has positively been found to have impact on students’ learning and personal growth, despite few academic setbacks. Thus, the study suggests that universities should establish structured systems to assist students to manage both academic and extracurricular responsibilities. Additionally, the results provide insightful information that students, university administrators, and educational officials may use to build a more stimulating and well-rounded learning environment.